Study Of Aspects Of Millennial Generation Employee Retention (Company Case Study PT. XYZ) - Ade Onny Siagian (Pelita : Jurnal Penelitian, Terapan dan Aplikatif, 2024)
In this study a case study method was used to analyze the factors of employee retention aimed specifically at millennial generation born between 1983 - 2000, or those under 36 years who worked at PT. XYZ This is because at this time the trend of 'turn over' of millennial generation employees is increasing, supported by secondary data from HRD which is quite large at around 14.3%. Data collection techniques in this study using a questionnaire with Likert scale calculations, and using descriptive interview techniques, namely interview techniques by making approaches. Respondents in this study were employees of PT. XYZ numbered 80 respondents representing various divisions and departments.